Pengaruh Skeptisme Profesional, Independensi Dan Pengalaman Auditor Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan: Studi Kasus Pada Kantor Akuntan Publik di Kota Pekanbaru - Raymondus Michael Sinaga; Annie Mustika Putri; Dwi Fionasari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study to examine the effect of professional skepticism, Independence and auditor experience afecct auditor’s ability to detect fraud at Public Accounting Firm in Pekanbaru city. The sample used are 55 auditors. The sample in this research was determined by the method sensus sampling technique. The research method used was quantitative. Data were collected using questionnaires. Data analysis technique used is Multiple Linear Regression Analysis. The results show that partially professional skepticism and Independence have significant effect on auditor’s ability to detect fraud. Auditor experience has no significant effect on the auditor's ability to detect fraud. Professional skepticism, Independence, and auditor experience simultaneously have a significant effect on the auditor's ability to detect fraud.